Phosphate solubilising Streptomyces spp obtained from the rhizosphere of Ceriops decandra of Corangi mangroves - SUBHASHINI, D V; V, ANIL KUMAR (The Indian Journal of Agricultural Sciences, 2014)
Phosphate-solubilizing potential of Streptomyces spp isolated from the rhizosphere soil of Ceriops decandra (Griffth) Ding Hou mangrove plant was studied using culture media supplemented with insoluble tricalcium phosphate which became transparent after few days of incubation. Fifteen phosphate-solubilizing strains of Streptomyces St-1 to St-15 were isolated from the rhizosphere of mangroves during 2010-11. Phosphate-solubilizing activity of these isolates was evaluated by the formation of halos (clear zones) around the colonies growing on solid medium containing tribasic calcium phosphate as a sole phosphorus source. St-3 was the most active phosphate solubilizing strain among the isolates followed by St-11. Studies on the biomass production of St-3 and St-11 showed an increase in growth at pH 7.2 after 7, 15 and 21 days of incubation at temperature 30°C and 37°C. Culture filtrate of St-3 alone showed the production of IAA. Present study reveals that the production of organic acids by the mangrove rhizosphere microorganisms may be a possible mechanism involved in the solubilization of insoluble calcium phosphate.